The wild Christmas reindeer - Brett, Jan, 1949- (New York : Putnam, 1990)
After a few false starts, Teeka discovers the best way to get Santa's reindeer ready for Christmas Eve.
4.3
K-3
K-3
Wilson's Children
Elem. School Library Collection
School Library Journal
Keywords: Reindeer -- Fiction; Christmas -- Fiction; Reindeer -- Fiction; Christmas -- Fiction